Pengaruh Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Fraudelent Financial Reporting - Mita Agustiana; Luke Suciyati Amna (Jurnal Ilmiah Akuntansi Kesatuan, 2023)
This study aims to determine the application of accounting information systems and internal controls to prevent fraudulent financial reporting case studies at PT. Nusantara Plantation VII. This research technique uses quantitative methods and data collection uses a questionnaire. The samples involved were several workers from 3 monetary divisions in the association with an aggregate of 45 respondents. The testing procedure used is purposive sampling. Data analysis for this study used multiple linear regression tests. The results of the study show that the application of accounting information systems and internal controls has a positive and significant impact on preventing fraudulent financial reporting.